Synergistic antimicrobial activity of melittin with clindamycin on the expression of encoding exfoliative toxin in Staphylococcus aureus. (August 2020) - Mahmoudi, Hassan; Alikhani, Mohammad Yousef; Imani Fooladi, Abbas Ali
Abstract: Staphylococcus aureus is an opportunistic human pathogens, with the ability to produce a series of virulence factors that contribute to the severity of infections. Exfoliative toxins (ETs) are one of the important virulence factors that participating in staphylococcal scalded skin syndrome. Melittin has different biological activities, comprising of antiviral, broad spectrum antibacterial, antiprotozoal, antifungal and anti-inflammatory effects. Twelve clinical isolates of methicillin-resistant S. aureus (MRSA) and methicillin-susceptible S. aureus (MSSA) were obtained from wound infection in the burn patients. The MIC plus three sub-inhibitory concentrations (I, II and III) of clindamycin and melittin were tested. Next, the synergistic effects of melittin and clindamycin were evaluated using the broth microdilution checkerboard assay. The detection of exfoliative toxin A and B genes were examined by PCR method. Then the effects of sub-MIC melittin on the expression levels of eta and etb were assessed by quantitative real-time PCR (qRT-PCR) assay. Melittin MIC values against MRSA and MSSA planktonic cells were 0.25–0.5 and 0.25–1 μg/ml, respectively. The clindamycin MIC values against MRSA and MSSA were between 0.5 and 8 μg/ml and 0.5–2 μg/ml, respectively. The results of the time-kill kinetics assay (3.5log10 and 3log10 ) against MSSA and MRSA planktonic cells were determined within 24 h using melittin. The mean expression of eta in MRSA and MSSA was significantly downregulated to approximately 3.5 and 4 fold, respectively. Moreover, the mean expression of etb in MRSA and MSSA were significantly downregulated to approximately 2.5 and 3 fold, respectively. Hemolytic assay showed that the extracted melittin indicates a strong hemolytic activity (HD50 = 2 μg/ml). Melittin at 0.5 μg/ml induced cell lysis and stimulated the formation of vesicles in S. aureus strains. Melittin could reduce the expression of eta and etb as encoding exfoliative toxin A and B genes. This component appears to be a good candidate for the treatment of MRSA and MSSA strains. So, melittin in combination with clindamycin can be classified as a complementary treatment of wound infections in burn patients. Highlights: Melittin showed in vitro antibacterial activity against clinical isolates of methicillin-resistant S. aureus (MRSA) and methicillin-susceptible S. aureus (MSSA). The combination of melittin and clindamycin have synergistic effects against S. aureus . Melittin reduced the expression of eta and etb as encoding exfoliative toxin A and B genes. Melittin induced cell lysis and stimulated the formation of vesicles in S. aureus strains.